Gene Spectrum and Clinical Traits of Nine Patients With Oocyte Maturation Arrest - Huo, Mingzhu; Zhang, Yile; Shi, Senlin; Shi, Hao; Liu, Yidong; Zhang, Lingyun; Wang, Yanchi; Niu, Wenbin (Frontiers in Genetics, 2022)
Background: Oocyte maturation arrest is a kind of disease that produces immature oocytes and cannot be mature after culturing in vitro, which leads to female primary infertility. We aimed to summarize nine representative patients in our center to retrospectively analyze the genetic variants and clinical characteristics of oocyte maturation arrest. Methods: This study examined and analyzed nine families with oocyte maturation arrest. Whole exome sequencing (WES) of the probands was performed to detect the pathogenic variants. Sanger sequencing verified the WES findings in patients and available parents. ExAC database was used to search the variant frequency. The variants were assessed by pathogenicity, conservational property prediction analysis and assessed according to the American College of Medical Genetics and Genomics (ACMG). Phenotypes of oocytes were evaluated by a light microscopy and the phenotype-genotype correlation was also evaluated. Results: Nine pathogenic variants in five genes were detected in nine patients, of which three were novel variants, including PATL2 [c.1374A>G (p. Ile458Met)] and [1289-1291del TCC (p. Leu430del)] and ZP2 [c.1543C>T (p. Pro515Ser)]. Nine variants were predicted to be pathogenic, resulting in different types of oocyte maturation arrest and clinical phenotypes. Conclusion: Three novel pathogenic variants were identified, which enables expanding the gene variant spectrum. The related pathogenic mutations of PATL2 gene, TUBB8 gene, and ZP1~3 gene were highly suggestive to be causative of oocyte maturation arrest.